THE IMPACT OF FDI INFLOW ON EMPLOYMENT IN V4 COUNTRIES - Brincikova, Zuzana; Darmo, Lubomir (European Scientific Journal, ESJ, 2014)
Paper´s effort is to analyse the impact of FDI inflow on employment of V4 countries by using panel data. This method allows us to evaluate the effect of FDI inflow on vacancies creation. Further, we discuss and explain the role of FDI inflow in this process with the focus on particularities of the V4 countries labour markets. Finally, paper discusses implications of FDI analysis and tries to verify the positive effect of FDI inflow on employment in V4 countries.